New species of Microspio Mesnil, 1896 (Annelida: Spionidae), with additions to the description of M. pigmentata (Reish, 1959) and comparative notes on all members of the genus - Maciolek, Nancy J.; Blake, James A. (Proceedings of the Biological Society of Washington, 2021)
Three new species of Microspio were found in collections from a range of depths including shallow water in Bermuda, the continental shelf off Massachusetts, and deep water in the South China Sea off Brunei. Microspio fischeri, new species, is associated with shallow water sponges in Bermuda where it is a prey species of a predatory syllid; it is characterized by the medial placement of the first pair of branchiae as well as unusual notopodial capillaries in anterior chaetigers and enlarged notopodial lobes in posterior chaetigers. Microspio lydonia, new species, from the continental shelf on the east coast of the United States is distinguished from M. pigmentata (Reish, 1959) from the west coast by differences in the structure of the nuchal organs and hooded hooks, pigmentation, and Methyl Green staining patterns. Additions to the description of M. pigmentata include illustration of the nuchal organs and dorsal ciliary bands. Microspio ariena, new species, from deep water in the South China Sea off Brunei has enlarged branchiae with large glands that stain deeply with Methyl Green on a few anterior chaetigers, followed by much smaller branchiae on additional chaetigers. The three new species bring the total of described species in the genus to twenty-one, although some species remain problematic. A table comparing important characteristics of all 21 known species of Microspio is included.
World Polychaeta Database (WPolyD).